Rapidly Growing Pancreatic Adenocarcinoma Presenting as an Irreducible Umbilical Hernia - Deepti M. Reddi; Kathryn P. Scherpelz; Angelica Lerma; Jabi Shriki; Jeffrey Virgin (Case Reports in Pathology)
Hernia sacs are a common anatomic pathology specimen, which rarely contain malignancy. We present a case of rapidly growing pancreatic adenocarcinoma, which initially presented as metastasis to an umbilical hernia sac. The patient was a 55-year-old male with a two-year history of umbilical hernia. Two months prior to herniorrhaphy, the hernia became painful and the patient experienced nausea and weight loss. The gross examination did not reveal distinct lesions. Microscopically, the hernia sac was diffusely infiltrated by moderately differentiated adenocarcinoma, which was positive for CK7 and pancytokeratin and negative for TTF-1, CK20, PSA, and CDX2. Clinical laboratory tests found elevated levels of CA 19-9 and CEA. Computed tomography scan with intravenous contrast showed a 5 cm ill-defined and hypoattenuating mass involving the pancreatic tail and body, as well as numerous ill-defined lesions in the liver and peritoneal carcinomatosis. The patient had an earlier noncontrast computed tomography scan four months prior to the surgery, which did not detect any lesions in the abdomen. This case highlights the importance of intravenous contrast with computed tomography for the evaluation of pancreatic lesions and also emphasizes the importance of thorough histologic evaluation of hernia sacs for the detection of occult malignancy.